2020
DOI: 10.1111/cen.14359
|View full text |Cite
|
Sign up to set email alerts
|

A survey of the young person’s experience of Graves’ disease and its management

Abstract: ObjectiveA suboptimal quality of life (QoL) has been reported in patients with Graves’ disease treated in adult life, but long‐term QoL in those treated in childhood and adolescence is unclear. We wanted to understand how Graves’ disease and its management impact on the physical, psychological and social well‐being of young people and their longer‐term QoL.Design, patients and measurementsTwo questionnaires were used to assess QoL and patient experience of Graves’ disease; PedsQL™ Generic Core Scales and a Gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 29 publications
(68 reference statements)
0
10
0
Order By: Relevance
“…In a recent study in young people who were diagnosed with and treated for GD in childhood, QoL was found to be lower than in healthy controls, especially in the psychosocial domain. Although more research on this topic is needed, it emphasizes the need for additional support for young people with GD, both at school and from a psychological perspective ( 98 ).…”
Section: Prognosismentioning
confidence: 99%
“…In a recent study in young people who were diagnosed with and treated for GD in childhood, QoL was found to be lower than in healthy controls, especially in the psychosocial domain. Although more research on this topic is needed, it emphasizes the need for additional support for young people with GD, both at school and from a psychological perspective ( 98 ).…”
Section: Prognosismentioning
confidence: 99%
“…The patient who is TPO antibody positive 1–2 years post antithyroid drug still needs monitoring to make sure that they remain euthyroid. There is relatively little data on quality of life in people with GD although a recent study has shown that young Graves’ patients have a lower total QoL score compared with a healthy cohort [ 45 ]. Individuals who chose definitive treatment with RAI or surgery did not regret this decision.…”
Section: Introductionmentioning
confidence: 99%
“…The short-term and long-term impact of GD on the young person from a physical, psychological and social perspective should not be underestimated. Indeed, patients with GD who were treated in childhood or adolescence report a lower quality of life than their healthy peers, particularly in the psychosocial domain 37. In addition, adult studies have reported that thyroid hormone replacement is associated with a reduced quality of life compared with controls 38.…”
Section: Quality Of Lifementioning
confidence: 99%